2021
DOI: 10.1140/epjd/s10053-021-00112-9
|View full text |Cite
|
Sign up to set email alerts
|

Submersion of rubidium clusters in helium nanodroplets

Abstract: Alkali atoms and small clusters are known to reside on the surface of a helium droplet rather than its inside as most other dopant species. A theoretical investigation suggested that alkali clusters (Li–Rb) exceeding a certain critical size can become submerged in the droplet, which was experimentally confirmed for sodium and potassium. Here, we report an analogous experimental study of rubidium cluster submersion by means of electron impact mass spectrometry. We recorded size distributions of Rb cluster ions … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…Droplets containing up to several billion helium atoms [ 16 , 17 , 18 ] can be formed via expansion of precooled pressurized helium through small nozzles into an ultra-high vacuum [ 19 , 20 ]. Evaporative cooling leads to an isothermal temperature of these droplets of about 0.4 K [ 21 ] and collisions with dopants lead to pickup and aggregation of these species to clusters [ 22 , 23 ] and nanoparticles [ 24 ] inside (heliophilic dopants) or on dimples at the surface of the helium droplets (heliophobic dopants) [ 25 , 26 ]. A convolution of the size distribution of the helium droplets and the Poisson pickup statistics lead to a broad log-normal size distribution of the dopant clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Droplets containing up to several billion helium atoms [ 16 , 17 , 18 ] can be formed via expansion of precooled pressurized helium through small nozzles into an ultra-high vacuum [ 19 , 20 ]. Evaporative cooling leads to an isothermal temperature of these droplets of about 0.4 K [ 21 ] and collisions with dopants lead to pickup and aggregation of these species to clusters [ 22 , 23 ] and nanoparticles [ 24 ] inside (heliophilic dopants) or on dimples at the surface of the helium droplets (heliophobic dopants) [ 25 , 26 ]. A convolution of the size distribution of the helium droplets and the Poisson pickup statistics lead to a broad log-normal size distribution of the dopant clusters.…”
Section: Introductionmentioning
confidence: 99%
“…Also shown is a similar transition for K clusters suggesting submersion into the HND around 80 K atoms [278]. Reproduced from [126]. Licensed under CC BY 4.0 ionization if they are located at or near the HND surface.…”
Section: Solvation Of Alkali Clusters In Hndsmentioning
confidence: 89%
“…Whereas the authors observed these larger clusters using single-PI with photon energies of 3.3 and 4.1 eV, no ions larger than trimers were detected using multi-PI at 1.4 eV. Familiar magic numbers such as n = 5, 9 and 19 are found for both species, with additional anomalies at n = 13, 21 and 28 for Rb n + [126] as well as n = 15 for Cs n + . Barring explicit evidence, the authors consider several models of cluster formation to argue that neutral alkali clusters should be able to form in both high and low spin states on the larger HNDs (<N> ~20,000) used in the experiment.…”
Section: Ernst Group (Graz)mentioning
confidence: 91%
See 2 more Smart Citations